Evaluating the State of the Employment Relationship: A Balanced Scorecard Approach Built on Mackenzie King’s Model of an Industrial Relations System - Kaufman, Bruce; Barry, Michael; Gomez, Rafael; Wilkinson, Adrian (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 2018)
The industrial relations (IR) field in Canada and the United States (US) emerged in the late 1910s-early 1920s and is thus on the cusp of its 100th anniversary. The impetus for the creation of the IR field was growing public alarm in both countries over the escalating level of conflict, violence, and class polarization in employer-employee relations. The two countries established federal-level government investigative committees, the Royal Commission on Industrial Relations (1919) in Canada and the Commission on Industrial Relations (1911-1915) in the US, to travel cross-country, gather evidence, and report their findings and overall evaluation.To commemorate the IR field’s centenary, this paper conducts the same type of cross-national ER evaluation, but with modern methods. First, this exercise requires a formal evaluation instrument, like a physical exam worksheet. Adopted is a modified version of a balanced scorecard. Second, the scorecard’s framework and questions should be theoretically informed. The framework used is a modified version of the diagrammatic model of an IR system presented by Mackenzie King in Industry and Humanity (1918). The third step is to fill in the scorecard with data from individual workplaces, which are obtained for the US from a new nationally-representative survey of 2000+ workplaces, the State of Workplace Employment Relations Survey (SWERS). The fourth step is to aggregate all the diagnostic measures to obtain a summary numerical estimate for each of the companies of its state of ER performance and health.Based on a 1-7 (7 = highest) scale, then converted to F to A grades, we find that the average ER grade given by managers is B+ and by employees C+. The company scores are graphed in a frequency distribution that visually represents, for the first time in the literature, the lowest-to-highest pattern of employment relations performance and health across the US.